Hidden and devalued feminised labour in the digital humanities - Nyhan, Julianne, author.
1 online resource (xi, 242 pages)
Keywords: Hidden and Devalued Feminized Labour in the Digital Humanities examines the data-driven labour that underpinned the Index Thomisticus-a preeminent project of the incunabular digital humanities-and advanced the data-foundations of computing in the Humanities. Through oral history and archival research, Nyhan reveals a hidden history of the entanglements of gender in the intellectual and technical work of the early digital humanities. Setting feminized keypunching in its historical contexts-from the history of concordance making, to the feminization of the office and humanities computing-this book delivers new insight into the categories of work deemed meritorious of acknowledgement and attribution and, thus, how knowledge and expertise was defined in and by this field. Focalizing the overlooked yet significant data-driven labour of lesser-known individuals, this book challenges exclusionary readings of the history of computing in the Humanities. Contributing to ongoing conversations about the need for alternative genealogies of computing, this book is also relevant to current debates about diversity and representation in the Academy and the wider computing sector. Hidden and Devalued Feminized Labour in the Digital Humanities will be of interest to researchers and students studying digital humanities, library and information science, the history of computing, oral history, the history of the humanities, and the sociology of knowledge and science.